Performance of midwives in providing midwifery services - Ida Ariyanti; Wien Sulistiyo Adi; Runjati Runjati (Jurnal Riset Kesehatan, 2012)
This research was descriptif exploratif desaign to study performace of midwives, population of this study was senior midwives who gave midwifery services that are partners of yunior midwives (graduated within 2 years). Sample found from 30 yunior midwives from Semarang city and 20 yunior midwives from subburb. Sample was given quisioner which asked performance evaluation and level competensi when giving services.The result of study showed that graduated midwives profiles majority 23 ages about 23 midwives (46%). Graduated midwives more work in independent midwives from profit institution about 34 midwives (68%), and experince doing midwifery services within 1 years.about 19 midwives (38%), and 0 yeras about 12 midwives (24%). Performance of midwives majority in enough category level about 28% midwives (56%). Otherwise level competency of midwives from midwifery services showed more than enough category level about 22 midwives (44%), and area that showe low achivement of competency was family planning implant device and intra uterin device.